The Role Of Social Capital and Local Institutions in Culture-Based Mangrove Ecotourism Governance in Berau Regency - Tamam Rosid (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
This study examines the integration of social capital, local institutions, and cultural values in mangrove ecotourism governance within Berau Regency, East Kalimantan. Employing a mixed-methods approach combining Structural Equation Modeling-Partial Least Squares (SEM-PLS), ecological carrying capacity analysis, and economic valuation, this research reveals how indigenous governance structures interact with modern sustainability frameworks. Primary data from 325 respondents across five coastal communities and secondary ecological data spanning 2022-2025 demonstrate that social capital significantly mediates the relationship between local institutional strength and community welfare outcomes (β=0.687, p<0.001). The ecological carrying capacity assessment indicates sustainable visitor thresholds ranging from 180 to 240 visitors per day across different mangrove zones. Economic analysis reveals that community-based ecotourism generates average monthly household income increases of 42.3% compared to pre-ecotourism baselines. The novelty of this research lies in its quantitative integration of cultural capital metrics, institutional quality indices, and tangible welfare indicators within a single analytical framework. Results demonstrate that communities with stronger traditional governance systems (adat institutions) achieve 34% higher sustainability scores and 28% greater income equity. Policy implications emphasize the necessity of hybrid governance models that formalize indigenous knowledge systems while maintaining cultural authenticity. This study contributes to sustainable development literature by providing empirical evidence for culture-based conservation approaches in tropical coastal ecosystems.